Factors Associated with Students’ Mental Health in Vocational Schools - Marisa Marisa; Nova Mardiana; Nurwijaya Fitri (Genius Journal, 2026)
Introduction: Mental health is a condition where a person is able to realize their own abilities, can cope with normal life pressures, can work productively and can contribute to their environment. Adolescence is a dynamic transition from childhood to adulthood, during which changes and challenges occur. These changes include physical, mental, social, and emotional changes. Objective: The purpose of this study was to determine the relationship between parenting patterns, bullying and social media on the mental health of students at SMK Negeri 1 Tukak Sadai, South Bangka Regency in 2025.  Method: The design in this study used cross-sectional with independent variables (parenting patterns, bullying and social media) and dependent variables (student mental health). The population size in this study was 315 people and a sample of 83 people calculated using cluster sampling. The time of the study was May 5, 2025 Result: The results of the study using the Chi Square statistical test obtained a p-value for the parenting variable 0.000 <0.05, bullying 0.000 <0.05 and social media 0.000 <0.05. This shows that there is a significant relationship between parenting patterns, bullying and social media on the mental health of students at SMK Negeri 1 Tukak Sadai, South Bangka Regency in 2025. Conclusion: Suggestions in this study are expected to make School Health Effort activities a step in monitoring health and anticipating early detection of the risk of poor mental health.